Using genetics to explore complement C5 as a druggable protein in periodontitis - Alayash, Zoheir; Baumeister, Sebastian-Edgar; Holtfreter, Birte; Kocher, Thomas; Baurecht, Hansjörg; Ehmke, Benjamin; Reckelkamm, Stefan Lars; Nolde, Michael (Frontiers in Immunology, 2024)
Aim: Excessively activated or dysregulated complement system has been proven to be a vital contributor to the pathogenesis of periodontitis. It has been previously hypothesized that inhibiting the activity of complement component C5 by targeting the C5a receptor is a powerful candidate for treating periodontitis. Here, we apply the drug target instrumental variable (IV) approach to investigate the therapeutic effect of genetically proxied inhibition of C5 on periodontitis. Method: In our primary analysis, we used 26 independent 'cis' single nucleotide polymorphisms as IVs from the vicinity of the encoding locus of C5 that are associated with plasma C5 levels. In a secondary analysis, we assess the validity of our primary findings, exploring the involvement of alternative downstream biomarkers, interleukin 17 (IL-17), interleukin 1β (IL-1β), and tumor necrosis factor (TNF). Summary statistics of plasma levels (C5, IL-17, IL-1β, and TNF) were obtained from genome-wide association study (GWAS) of 35,559 European descent individuals. We extracted association statistics from a GWAS of 17,353 clinical periodontitis cases and 28,210 European controls. Wald ratios were combined using inverse-variance weighted meta-analysis. Results: In our primary approach, inhibiting C5 reduced the risk of periodontitis (Odds ratio 0.89 per 1 standard deviation reduction in C5; 95% confidence Interval 0.80-0.98, p value=0.022). Our secondary analysis suggests an involvement of IL-17 within the potential causal pathway, but was inconclusive for other biomarkers. Conclusions: The findings from our study suggest that C5 inhibition may reduce the risk of periodontitis, prioritizing C5 inhibitors as a potential adjunctive therapeutic intervention in this disease.